Emerging targets of inflammation and tear secretion in dry eye disease. Issue 8 (August 2019) - Markoulli, Maria; Hui, Alex
Highlights: Dry eye management aims to restore tear film homeostasis. Many current treatment options are largely palliative. Two emerging treatment areas aim to promote tear secretion and manage inflammation. This review focuses on secretagogues and lymphocyte-function-associated antigen-1 antagonists. Abstract : The underlying mechanisms of dry eye are thought to be part of a vicious circle involving a hyperosmolarity-triggered inflammatory cascade, resulting in loss of goblet cells and glycocalyx mucin and observed corneal and conjunctival epithelial cell damage. This damage leads to increased tear film instability, further hyperosmolarity and hence perpetuating of a vicious circle. The aim of dry eye management is to restore the homeostasis of the tear film and break the perpetuation of this vicious circle. Despite the plethora of treatment options available, many of these are largely palliative, short-lived and require repeated instillations. Two emerging areas in dry eye therapy aim to promote tear secretion and to safely manage dry eye-associated inflammation and are the focus of this review.